MENINGKATKAN HASIL BELAJAR EKONOMI MATERI JURNAL PENYESUAIAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DEVISIONS (STAD) PADA SISWA KELAS XI IPS 4 DI SMAN 1 BARABAI TAHUN PELAJARAN 2013/2014 - Endang Sulistiawati (Universitas Lambung Mangkurat, 2014)
The research aimed are: (1)Increasing the learning outcomes of students class XI Social Science 4 on Economic course by using STAD model of cooperative learning, (2) Describing the activities of the students of class XI IPS 4 by using STAD model, (3)Describing the application of STAD model on Economic course for the students of class XI IPS 4. This research also designed and prepared by using action research. The subjects were the students of class XI IPS 4 SMAN 1 in Barabai year 2013/2014. Meanwhile, the objects for the research were the learning outcomes and students’ activities in the application of STAD model of cooperative learning. As the result showed that: (1) Students’ learning outcomes of economic course of class XI IPS 4 of SMAN 1 Barabai year 2013 / 2014 can be increased by using Students Team Achievement Divisions (STAD) model of cooperative learning, with learing success of 91.18%, (2) Students’ activeness was achieved by using the model in which 80% of students were in active classification and in considerable active as much as 20%, (3) The quality aspects of the teaching and learning management conducted by the teacher by using the model was optimal, namely as much as 66.68% was in good classification, whereas 33.33% was in very good classification.Keywords : Learning Outcomes, Economics Subject, Cooperative Learning, STAD Model